Rethinking Migration and Return in Southeastern Europe Albanian Mobilities to and from Italy and Greece - Gemi, Eda (Taylor & Francis, 2021)
This book provides an important new analytical framework for making sense of return, remigration and circular mobility, conceptualising them as different phases of a wider migration process. Using an in-depth case study of Albania and its two main destination countries, Italy and Greece, the book demonstrates that instead of being viewed as a linear path between origin and destination, migration should be seen as a segmented, or cyclical pattern that may involve several localities and more than two countries. Characterised by important previous historical, social, economic and political linkages, geographical proximity but also high migration volatility and sustained flows in either directions, Albanian migration to Italy and Greece offers an optimal case study for analysing complex return, reintegration and mobility processes. While interesting as a unique regional migration system, the lessons learned cast light on important migration and mobility dynamics that are relevant for labour migration in Europe, also from other important migrant origin countries in the EU's neighbourhood such as for instance Morocco or the Ukraine. This rich theoretical and empirical study will be of interest to researchers within European Studies and Migration Studies, as well as providing a useful contribution to policy debates on how to govern return migration, reintegration and circular migration.